PENGETAHUAN PEMUSTAKA DI UPT PERPUSTAKAAN PROKLAMATOR BUNG KARNOTENTANG BIOGRAFI BUNG KARNO - Kristiana, Nina (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2024)
One of the functions of the Proklamator Bung Karno Library is to utilize the Bung Karno Literature Collection. The utilization in question is not just achieving a high number of visits by users to the Special Collection about Bung Karno, but more than that. The utilization in question is the effort so that users increase their knowledge of Bung Karno's Biography. Indicators of the library's success in carrying out this function can be seen, among others, from the knowledge of users about Bung Karno. Therefore, this study aims to determine the knowledge of users about Bung Karno's biography. This study uses a quantitative descriptive method through a questionnaire containing closed questions about Bung Karno's biography. The results of the study involving 254 respondents showed that on the first question about Bung Karno's date of birth, 156 respondents answered correctly, 83 respondents answered incorrectly, and 15 respondents did not answer; the second question about Bung Karno's place of birth, 132 respondents answered correctly, 105 respondents answered incorrectly, and 17 respondents did not answer; to the third question about Bung Karno's father's name, 130 respondents answered correctly, 109 respondents answered incorrectly, and 15 respondents did not answer; to the fourth question about Bung Karno's mother's name, 123 respondents answered correctly, 116 answered incorrectly, and 15 respondents did not answer; the fifth question about Bung Karno's first name, 124 respondents answered correctly, 115 respondents answered incorrectly, and 15 respondents did not answer; the sixth question about the date Bung Karno died, 108 respondents answered correctly, 130 respondents answered incorrectly, and 16 respondents did not answer; on the seventh question about the name of Bung Karno's native school, 89 respondents answered correctly, 148 respondents answered incorrectly, and 17 respondents did not answer; to the eighth question about the name of Bung Karno's first wife, 84 respondents answered correctly, 154 respondents answered incorrectly, and 16 respondents did not answer; The ninth question about the major taken by Bung Karno while studying at THS, 143 respondents answered correctly, 94 respondents answered incorrectly, and 17 respondents did not answer; the tenth question about the relationship between Bung Karno and Pancasila, 85 respondents answered correctly, 155 respondents answered incorrectly, and 14 respondents did not answer. From all the respondents' answers, it was found that the percentage of correct answers from respondents was 46%, incorrect answers 48%, and unanswered questions were 6%. The predicate value obtained was D which means less, because the percentage of correct answers was less than 60. The conclusion of this study is that the knowledge of the users of the Proklamator Bung Karno Library about the biography of Bung Karno is still low or lacking. Therefore, various efforts need to be made to improve the knowledge of users about the biography of Bung Karno, especially to carry out the functions carried out by the Proklamator Bung Karno Library.